2007
DOI: 10.1186/1472-6963-7-146
|View full text |Cite
|
Sign up to set email alerts
|

Severe mental illness and mortality of hospitalized ACS patients in the VHA

Abstract: Background: Severe mental illness (SMI) has been associated with more medical co-morbidity and less cardiovascular procedure use for older patients with myocardial infarction. However, it is unknown whether SMI is associated with increased long term mortality risk among patients presenting with acute coronary syndromes (ACS). We tested the hypothesis that SMI is associated with higher one-year mortality following ACS hospitalization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
31
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 21 publications
1
31
0
Order By: Relevance
“…Finally, prior publications 32 indicate that depression increases the risk of delirium Our findings of the risk of 30-day mortality associated with a comorbid psychiatric condition are consistent with the results of studies in veterans hospitalized for AMI by Plomondon et al 1 and Peterson et al, 3 who did not find an increased risk of 30-day mortality among patients with a comorbid psychiatric condition. In contrast to these prior studies, we found a modest association of preexisting comorbid psychiatric conditions with in-hospital mortality, although our study was powered to detect small differences in mortality between patients with and without comorbid psychiatric conditions relative to these prior studies.…”
Section: Discussionsupporting
confidence: 82%
See 3 more Smart Citations
“…Finally, prior publications 32 indicate that depression increases the risk of delirium Our findings of the risk of 30-day mortality associated with a comorbid psychiatric condition are consistent with the results of studies in veterans hospitalized for AMI by Plomondon et al 1 and Peterson et al, 3 who did not find an increased risk of 30-day mortality among patients with a comorbid psychiatric condition. In contrast to these prior studies, we found a modest association of preexisting comorbid psychiatric conditions with in-hospital mortality, although our study was powered to detect small differences in mortality between patients with and without comorbid psychiatric conditions relative to these prior studies.…”
Section: Discussionsupporting
confidence: 82%
“…We then excluded 18 057 patients without any VHA outpatient C omorbid psychiatric conditions are common among patients admitted to acute care hospitals. [1][2][3][4][5][6][7] Estimates of the impact of such comorbid conditions on hospital outcomes, however, are less clear. Although results of some studies 4,[8][9][10][11][12] indicate that patients with comorbid psychiatric conditions are subject to higher mortality and less likely to receive guideline-recommended care after admission for acute myocardial infarction (AMI), other studies 1,3,7 have not shown such disparities.…”
Section: Population Of Patientsmentioning
confidence: 99%
See 2 more Smart Citations
“…14 -18 However, other studies have failed to detect such relationships. 19,20 One potential explanation for the inconsistencies in the associations between AMI-related hospital outcomes and psychiatric comorbidities may be the methodological approach that has been used to identify psychiatric comorbidity from administrative databases. Therefore, we completed this study to directly evaluate how different approaches of identifying psychiatric comorbidities may impact AMI-related hospital outcomes for a range of psychiatric conditions.…”
mentioning
confidence: 99%